2015
DOI: 10.1177/1533034615582290
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy of Hodgkin and Non-Hodgkin Lymphoma

Abstract: Purpose: To improve the contouring of clinical target volume for the radiotherapy of neck Hodgkin/non-Hodgkin lymphoma by localizing the prechemotherapy gross target volume onto the simulation computed tomography using [18 F]-fluorodeoxyglucose positron emission tomography/computed tomography. Material and Methods: The gross target volume delineated on prechemotherapy [18 F]-fluorodeoxyglucose positron emission tomography/computed tomography images was warped onto simulation computed tomography using deformabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…PET/CT can clearly indicate active regions of tumor metabolism and liquefaction of a necrotic area, in addition to accurately delineating tumor radiotherapy target volume that can help guide the radiation field and radiation dose distribution design, in order to prevent normal tissues from receiving unnecessary irradiation and improve the efficacy of tumor radiotherapy. [2930] Nam et al . [31] reported that the PET/CT plan was better than the conventional point A plan in terms of target coverage without subjecting the normal tissue to an increased dose, which made optimized three-dimensional (3D) brachytherapy treatment planning possible.…”
Section: Positron Emission Tomography/computed Tomography Imaging Fusmentioning
confidence: 99%
“…PET/CT can clearly indicate active regions of tumor metabolism and liquefaction of a necrotic area, in addition to accurately delineating tumor radiotherapy target volume that can help guide the radiation field and radiation dose distribution design, in order to prevent normal tissues from receiving unnecessary irradiation and improve the efficacy of tumor radiotherapy. [2930] Nam et al . [31] reported that the PET/CT plan was better than the conventional point A plan in terms of target coverage without subjecting the normal tissue to an increased dose, which made optimized three-dimensional (3D) brachytherapy treatment planning possible.…”
Section: Positron Emission Tomography/computed Tomography Imaging Fusmentioning
confidence: 99%